2009
DOI: 10.1002/mas.20224
|View full text |Cite
|
Sign up to set email alerts
|

Infrared consequence spectroscopy of gaseous protonated and metal ion cationized complexes

Abstract: In this article, the new and exciting techniques of infrared consequence spectroscopy (sometimes called action spectroscopy) of gaseous ions are reviewed. These techniques include vibrational predissociation spectroscopy and infrared multiple photon dissociation spectroscopy and they typically complement one another in the systems studied and the information gained. In recent years infrared consequence spectroscopy has provided long-awaited direct evidence into the structures of gaseous ions from organometalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
179
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 142 publications
(147 reference statements)
3
179
0
Order By: Relevance
“…Over the past number of years, IRMPD spectroscopy has proven to be a valuable tool for obtaining structural insight into protonated and metal ion complexes of small biological molecules including amino acids, nucleobases, and peptides [71][72][73]. In this study, the technique is used in combination with computational methods to determine the structure of a lithium-A:T base pair complex as solvated by one water molecule.…”
Section: Introductionmentioning
confidence: 98%
“…Over the past number of years, IRMPD spectroscopy has proven to be a valuable tool for obtaining structural insight into protonated and metal ion complexes of small biological molecules including amino acids, nucleobases, and peptides [71][72][73]. In this study, the technique is used in combination with computational methods to determine the structure of a lithium-A:T base pair complex as solvated by one water molecule.…”
Section: Introductionmentioning
confidence: 98%
“…One of the most powerful techniques for this purpose is infrared multiple photon dissociation (IRMPD) spectroscopy [16,17]. Since infrared photodissociation is only induced when the impinging photon is of a resonant energy with a vibrational mode of the analyte, by recording photofragmentation as a function of photon energy, an IRMPD spectrum, analogous to a more traditional absorption IR spectrum, can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…I nfrared multiple photon dissociation (IRMPD) spectroscopy [1][2][3] is one of the most useful tools in elucidating the chemistry of peptide dissociation in the gas phase by virtue of chemically diagnostic vibrations that can be identified [4]. One of the "textbook" examples of this approach involves verifying the oxazolone structure of "b" fragment ions [5,6] formed from collision-induced dissociation (CID) of protonated peptides.…”
Section: Introductionmentioning
confidence: 99%
“…For the smallest b 2 fragments, such cyclic structures are known as diketopiperazine structures [16]. The majority of IRMPD spectroscopy studies on b 2 fragments have so far identified oxazolone structures [9,10,13,14]; however, for instance for histidine-containing b 2 , a mixture of oxazolone and diketopiperazine structures was confirmed [12]. All IRMPD spectroscopy studies described above have been carried out at the free electron laser (FEL) facilities FELIX in The Netherlands or CLIO in France [17,18].…”
Section: Introductionmentioning
confidence: 99%